KERAGAAN USAHATANI VARIETAS UNGGUL BARU (VUB) PADI SAWAH DENGAN POLA PENGELOLAAN TANAMAN TERPADU (PTT):STUDI KASUS DI DESA ANEUK GLEE KECAMATAN INDRAPURI NANGGROE ACEH DARUSSALAM - Fauzi, Emlan; Andani, Apri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2010)
This research aims to determine the performance of new varieties of farm (VUB), lowland rice through an integrated approach to crop management (ICM) in the village of Gle Aneuk Indrapuri, Aceh Besar District. Field assessment is from cooperative farmers who have lowland rice varieties with treatment, such as Cimelati, Bondoyudo, Ciherang, Kalimas, VUTB Fatmawati and IR-64. In each of these rice varieties applied packages introduced PTT technology. The result indicates that reviewed the six varieties suitable for cultivated and developed. Judging from the performance of agronomic VUTB Fatmawati better compared with 5 other varieties. VUTB Fatmawati have the greatest production (7.75 tonnes / ha) with a profit-making Rp.6.074.750, -. Fatmawati lowland rice farming system with ICM pattern is more feasible to be developed because the RC has the largest ratio (2.09) compared with the varieties Cimelati (2,06), Kalimas (2,04), Bondoyudo (2,02), Ciherang (1,51) and varieties of IR-164 (1,39).